Glycolate combats massive oxidative stress by restoring redox potential in Caenorhabditis elegans - Veronica Diez (Nature Portfolio, 2021)
Diez et al. show that glycolate suppresses deleterious effects of peroxide on mitochondrial activity and growth of worms. They find that the conversion of glycolate into glycine and serine helps worms maintain cellular antioxidants following oxidative stress. This study suggests that glycolate serves as a natural antioxidant improving organismal fitness under stress.